An Acculturation Review of the Population Phenomenon in the Formation of Cultural and Religious Traditions in Yogyakarta - ashri_paper (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article discusses the Acculturation Review of the Immigrant Population Phenomenon, in the Formation of Cultural and Religious Traditions in Yogyakarta. Given that the wealth of deep cultural and religious traditions in Yogyakarta, not only becomes the center of attention in the context of social change. However, the presence of immigrant populations in the city not only brings new challenges, but also opens up opportunities for acculturation. This article focuses on the significant influence of immigrant populations on the transformation of long-established cultural traditions and religious practices. Through a qualitative approach, the research applies in-depth interviews and participatory observation in several immigrant communities, to explore the interactions that occur between immigrants and local people. The results show that immigrant populations not only adopt local traditions, but also actively contribute to enriching and modifying cultural and religious practices. This acculturation process creates a unique blend of cultural elements and generates new dynamics in the social life of the people of Yogyakarta. As such, this research provides important insights into intercultural interactions and how these relationships shape collective identity in a multicultural society. The findings provide a foundation for further understanding of how diversity can be managed and celebrated, and how the process of acculturation can be a bridge to create harmony in a diverse society.